2019
DOI: 10.1103/physrevb.100.064409
|View full text |Cite
|
Sign up to set email alerts
|

HT phase diagram of rare-earth–transition-metal alloys in the vicinity of the compensation point

Abstract: Anomalous hysteresis loops of ferrimagnetic amorphous alloys in high magnetic field in the vicinity of the compensation temperature have so far been explained by sample inhomogeneities. We obtain the H-T magnetic phase diagram for the ferrimagnetic GdFeCo alloy using a two-sublattice model in the paramagnetic rare-earth ion approximation and taking into account rare-earth (Gd) magnetic anisotropy. It is shown that if the magnetic anisotropy of the f sublattice is larger than that of the d sublattice, the tricr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Earlier studies of rare-earth ferrimagnets have found that in the case of weak rare-earth magnetic anisotropy the transition shifts towards the lower temperatures with the increase of the magnetic field 35 . On the other hand, from more general considerations we have shown 19,26,36 that if the rare-earth anisotropy is prevailing an inclination of the first-order phase transition line towards higher temperatures would occur; therefore, we assume that the surface anisotropy introduced by Ta capping influences d-states that relatively more delocalized, and thus, for Ta-coated TbFeCo the f-sublattice anisotropy doesn't dominate at least in the vicinity of the compensation temperature of the film. The physical reason behind this is that Ta, electronic configuration of which is [Xe] 4f 14 5d 3 6s 2 , has large atomic number Z = 73 and spin-orbit coupling scales approximately as Z 4 [ 37 ].…”
Section: Discussionmentioning
confidence: 94%
“…Earlier studies of rare-earth ferrimagnets have found that in the case of weak rare-earth magnetic anisotropy the transition shifts towards the lower temperatures with the increase of the magnetic field 35 . On the other hand, from more general considerations we have shown 19,26,36 that if the rare-earth anisotropy is prevailing an inclination of the first-order phase transition line towards higher temperatures would occur; therefore, we assume that the surface anisotropy introduced by Ta capping influences d-states that relatively more delocalized, and thus, for Ta-coated TbFeCo the f-sublattice anisotropy doesn't dominate at least in the vicinity of the compensation temperature of the film. The physical reason behind this is that Ta, electronic configuration of which is [Xe] 4f 14 5d 3 6s 2 , has large atomic number Z = 73 and spin-orbit coupling scales approximately as Z 4 [ 37 ].…”
Section: Discussionmentioning
confidence: 94%
“…, where g is Lande g-factor, J is total angular momentum of the rare-earth ions, µ B is Bohr magneton. The anisotropy energy of the ferrimagnet is [14,19]:…”
Section: Model and Basic Equationsmentioning
confidence: 99%
“…Recent researches show that anisotropy of the RE sublattice can be larger then the one of the TM sublattice [19]. Therefore, let us investigate how lines of the first and second phase transitions are changed due to the exchange surface anisotropy.…”
Section: Magnetic Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…Very rich and interesting magnetization dynamics [13,14], in terms of fundamental and applied * zvezdin.ka@phystech.edu physics, is observed in these materials near the points of compensation of magnetization and angular momentum. Moreover, by manipulating the temperature of the ferrimagnet near the compensation points, outstanding magnetization switching characteristics can be obtained [15][16][17]. It has been shown that the electrical current can be an efficient approach to magnetization switching [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%